Prevention of chronic postoperative pain syndrome after Lichtenstein hernioplasty - A. V. Yuri; D. S. Tevs; N. R. Kopteev; D. A. Tishenko; D. K. Zakharova; B. B. Orlov; V. A. Kashchenko (Вестник хирургии имени И.И. Грекова)
THE OBJECTIVE was to analyze the development of chronic pain syndrome after performing standardized Lichtenstein hernioplasty.METHODS AND MATERIALS. The prospective single-center study was conducted with 40 patients with inguinal hernias (20 patients in the study group and 20 patients in the control group) who underwent Lichtenstein hernioplasty with adherence to standardization criteria and without. The comparative analysis of the early and long-term postoperative periods was performed.RESULTS. When comparing the early and long-term postoperative periods in patients after standardized Lichtenstein hernioplasty, the following data were obtained: pain syndrome according to the Visual Analogue Scale (VAS) was less pronounced after applying standardization criteria (p < 0.001), and statistically significantly lower number of complications (seroma, paresthesia) developed (p=0.045, p=0.019). In the group of patients who underwent standardized Lichtenstein hernioplasty, chronic pain syndrome was not observed in the long-term postoperative period (p < 0.001).CONCLUSIONS. Prevention of chronic postoperative pain syndrome after hernioplasty using the Lichtenstein method is the significant issue. This article emphasizes the importance of considering various factors and implementing preventive strategies to minimize the risk of this complication and ensure optimal surgical outcomes.